2020
DOI: 10.1002/jcla.23677
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin enhances the antitumor efficacy of oncolytic vaccinia virus that harbors IL‐24 gene in liver cancer cells

Abstract: The pathogenesis of liver cancer involves genetic and epigenetic alterations. Usually, treatments such as surgical resection, local ablation and chemotherapy can only be effective in the early stage, but no therapies are available for advanced liver cancer. 1 Liver cancer is complex since it involves modifications and cross-talk among several signal pathways. 2 Therefore, the development of combination therapy could provide superior treatment for liver cancer in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Liver cancer is the world's third largest cause of cancer mortality [ 65 ]. The burden and aetiology of liver diseases have changed during the last decade [ 66 , 67 ]. In this respect, Cao et al (2018) showed that luteolin reduces the SMMC-7721 cell viability in a time- and dose-dependent fashion.…”
Section: Anticancer Properties Of Luteolin and Its Mechanism Of Actionmentioning
confidence: 99%
“…Liver cancer is the world's third largest cause of cancer mortality [ 65 ]. The burden and aetiology of liver diseases have changed during the last decade [ 66 , 67 ]. In this respect, Cao et al (2018) showed that luteolin reduces the SMMC-7721 cell viability in a time- and dose-dependent fashion.…”
Section: Anticancer Properties Of Luteolin and Its Mechanism Of Actionmentioning
confidence: 99%
“…Cancer-targeting gene-viro therapy (CTGVT), which uses oncolytic viral vectors that encode anticancer genes, has been shown to have potent anticancer activities [ 113 ]. In a study by Wang et al, 2021, the researchers used oncolytic vaccinia virus (VV) that encoded the IL-24 gene (VV-IL-24) as the model for CTVGT in the treatment of liver cancer and investigated the potential synergistic effect of Luteolin to the treatment [ 114 ]. The study revealed that the combination of VV-IL-24 and Luteolin caused a stronger decrement in the viability and induction of apoptosis of liver cancer cells compared to Luteolin or VV-IL-24 alone.…”
Section: Anticancer Properties Of Luteolin On Different Cancersmentioning
confidence: 99%
“…The study revealed that the combination of VV-IL-24 and Luteolin caused a stronger decrement in the viability and induction of apoptosis of liver cancer cells compared to Luteolin or VV-IL-24 alone. Additionally, in the MHCC97-H xenograft liver cancer model, combination treatment resulted in significant tumor reduction compared to a single treatment, exhibiting the synergistic mechanism employed by VV-IL-24 and Luteolin to treat liver cancer [ 114 ].…”
Section: Anticancer Properties Of Luteolin On Different Cancersmentioning
confidence: 99%
“…Due to its special molecular characteristics, endocrine therapy and molecular targeted therapy, along with other treatment approaches, have not been effective in the clinical treatment of TNBC, leading to high rates of distant recurrence and mortality (9,11,12). In recent years, researchers have focused on TNBC and other cancer treatments and have made several progress (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%